Is there a threat of self-reinforcing deflation in the euro area? A view through the lens of the Phillips curve - Volker Wieland; Maik Wolters (Kiel Institute for the World Economy (IfW), 2014)
The recent decline in euro area inflation has triggered new calls for additional monetary stimulus by the ECB in order to counter the threat of a self-reinforcing deflation and recession spiral. This note reviews the available evidence on inflation expectations, output gaps and other factors driving current inflation through the lens of the Phillips curve. It also draws a comparison to the Japanese experience with deflation in the late 1990s and the evidence from Japan concerning the output-inflation nexus at low trend inflation. The note concludes from this evidence that the risk of a self-reinforcing deflation remains very small. Thus, the ECB best await the impact of the long-term refinancing operations decided in June that have the potential to induce substantial monetary accommodation once implemented for the first time in September.
Keywords: 330